Development of functionalized nanoparticles for vaccine delivery to dendritic cells: a mechanistic approach. (December 2014) - Silva, Joana M; Vandermeulen, Gaëlle; Oliveira, Vanessa G; Pinto, Sandra N; Rodrigues, Catarina; Salgado, Ana; Afonso, Carlos A; Viana, Ana S; Jérôme, Christine; Silva, Liana C; Graca, Luis; Préat, Véronique; et al.
Aim: Produce biodegradable nanoparticles to target antigen-presenting cells (APCs) and evaluate their potential to be used as a vaccine delivery system.Materials & methods: Untargeted PEGylated poly(d, l -lactic- co -glycolide)-based nanoparticles and mannose-grafted nanoparticles were formulated and physicochemically characterized. Immortalized and primary APCs were used to study nanoparticle internalization patterns. The endocytic pathways and intracellular trafficking followed by nanoparticles were also investigated.Results & discussion: Nanoparticles displayed mannose residues available for binding at the nanoparticle surface. Different nanoparticle internalization patterns by immortalized and primary APCs were verified. Macropinocytosis, clathrin-mediated endocytosis, caveolin- and lipid raft-dependent endocytosis are involved in nanoparticles internalization. Nanoparticles demonstrate both endolysosomal and cytosolic localizations and a tendency to accumulate nearby the endoplasmic reticulum.Conclusion: The developed nanoparticles might drive antigens to be presented through MHC class I and II molecules to both CD8 + and CD4 + T cells, favoring a complete and coordinated immune response.